The link between product market reform, innovation and EU macroeconomic performance - Griffith, Rachel; Harrison, Rupert; Simpson, Helen; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
Value-added per capita in EU countries has lagged behind the US. This is despite widespread reforms to product markets across EU countries aimed at increasing growth. This study analyses the macro-economic impact of product market reforms undertaken in the European Union over the 1980s and 1990s by examining a large number of regulations and reforms across EU countries.
Internal paper
Economic Papers